Use of CTX-I and PINP as bone turnover markers: National Bone Health Alliance recommendations to standardize sample handling and patient preparation to reduce pre-analytical variability - Szulc, P.; Naylor, K.; Hoyle, N. R.; Eastell, R.; Leary, E. T. (Osteoporosis international, 2017)
Summary The National Bone Health Alliance (NBHA) recommends standardized sample handling and patient preparation for C-terminal telopeptide of type I collagen (CTX-I) and N-terminal propeptide of type I procollagen (PINP) measurements to reduce pre-analytical variability. Controllable and uncontrollable patient-related factors are reviewed to facilitate interpretation and minimize pre-analytical variability. Introduction The IOF and the International Federation of Clinical Chemistry (IFCC) Bone Marker Standards Working Group have identified PINP and CTX-I in blood to be the reference markers of bone turnover for the fracture risk prediction and monitoring of osteoporosis treatment. Although used in clinical research for many years, bone turnover markers (BTM) have not been widely adopted in clinical practice primarily due to their poor within-subject and between-lab reproducibility. The NBHA Bone Turnover Marker Project team aim to reduce pre-analytical variability of CTX-I and PINP measurements through standardized sample handling and patient preparation. Methods Recommendations for sample handling and patient preparations were made based on review of available publications and pragmatic considerations to reduce pre-analytical variability. Controllable and un-controllable patient-related factors were reviewed to facilitate interpretation and sample collection. Results Samples for CTX-I must be collected consistently in the morning hours in the fasted state. EDTA plasma is preferred for CTX-I for its greater sample stability. Sample collection conditions for PINP are less critical as PINP has minimal circadian variability and is not affected by food intake. Sample stability limits should be observed. The uncontrollable aspects (age, sex, pregnancy, immobility, recent fracture, co-morbidities, anti-osteoporotic drugs, other medications) should be considered in BTM interpretation. Conclusion Adopting standardized sample handling and patient preparation procedures will significantly reduce controllable pre-analytical variability. The successful adoption of such recommendations necessitates the close collaboration of various stakeholders at the global stage, including the laboratories, the medical community, the reagent manufacturers and the regulatory agencies.